ANALISIS KELAYAKAN KEUANGAN PADA KOPERASI JASA KEUANGAN (KJK) PEMK RAMBUTAN JAKARTA TIMUR - Dhona Shahreza (Universitas Indraprasta PGRI, 2015)
This study aims to analyze the financial of feasibility in determining the healthy level of KJK PEMK Rambutan in East Jakarta. A descriptive quantitative method is employed which data is taken from the Income Statement and Balance Sheet of KJK PEMK Rambutan in East Jakarta from 2011 to 2013 using various instrument indicators, namely capital aspect, productivity of asset quality aspect, profitability aspect, liquidity aspect and also management aspect. The results show that: 1) In capital aspect, the value of equity capital to total assets ratio is increase while the ratio of equity capital to risky loans is decrease; 2) In productivity of asset quality aspect, loan volume of members to the total volume of loans ratio during the year remains stable, while the risk of bad debts to the total volume of loans ratio is fluctuative when the risk of reserve to the risk of bad debts ratio is decrease; 3) Based on profitability aspect, SHU before tax to Operating Income is increase while the ratio of SHU before tax to total assets is decrease, and Operating Expenses to Operating income ratio is also decreased; 4) Score of management aspect is 19; 5) In liquidity ratio, it is found that the ratio of total loans to the funds received is decrease; 5) Based on the cooperative healthy level assessment, it is found that KJK PEMK Rambutan of East Jakarta in 2011 and 2012 is less healthy while in 2013 is fairly healthy. Keywords: Financial Feasibility, Healthy Level, KJK, PEMK.